Endocannabinoids and Fear-Related Behavior in Mice Selectively Bred for High or Low Alcohol Preference - Aaron M. Kirchhoff; Eric L. Barker; Julia A. Chester (Brain Sciences, 2019)
Alcohol use disorders (AUDs) have a high incidence of co-morbidity with stress-related psychopathologies, such as post-traumatic stress disorder (PTSD). Genetic and pharmacological studies support a prominent role for the endocannabinoid system (ECS) in modulating stress-related behaviors relevant to AUDs and PTSD. Mouse lines selectively bred for high (HAP) and low (LAP) alcohol preference show reproducible differences in fear-potentiated startle (FPS), a model for PTSD-related behavior. The first experiment in this study assessed levels of the endocannabinoids, anandamide (AEA) and sn-2 arachidonylglycerol (2-AG), in the prefrontal cortex (PFC), amygdala (AMG), and hippocampus (HIP) of male and female HAP1 and LAP1 mice following the expression of FPS to determine whether ECS responses to conditioned-fear stress (FPS) were correlated with genetic propensity toward high or low alcohol preference. The second experiment examined effects of a cannabinoid receptor type 1 agonist (CP55940) and antagonist (rimonabant) on the expression of FPS in HAP1 and LAP1 male and female mice. The estrous cycle of females was monitored throughout the experiments to determine if the expression of FPS differed by stage of the cycle. FPS was greater in male and female HAP1 than LAP1 mice, as previously reported. In both experiments, LAP1 females in diestrus displayed greater FPS than LAP1 females in metestrus and estrus. In the AMG and HIP, AEA levels were greater in male fear-conditioned HAP1 mice than LAP1 mice. There were no line or sex differences in effects of CP55940 or rimonabant on the expression of FPS. However, surprisingly, evidence for anxiogenic effects of prior treatment with CP55940 were seen in all mice during the third drug-free FPS test. These findings suggest that genetic differences in ECS function in response to fear-conditioning stress may underlie differences in FPS expression in HAP1 and LAP1 selected lines.